2019
DOI: 10.1002/ppul.24603
|View full text |Cite
|
Sign up to set email alerts
|

Lung deposition of nebulized surfactant in newborn piglets: Nasal CPAP vs Nasal IPPV

Abstract: Background Nasal continuous positive airway pressure support (nCPAP) is the standard of care for prematurely born infants at risk of neonatal respiratory distress syndrome (nRDS). However, nasal intermittent positive pressure ventilation (NIPPV) may be an alternative to nCPAP in babies requiring surfactant, and in conjunction with surfactant nebulization, it could theoretically reduce the need for invasive mechanical ventilation. We compared lung deposition of nebulized poractant in newborn piglets supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…The authors reported that this intrapulmonary surfactant deposition sufficed to revert the respiratory distress in surfactant-depleted adult rabbits [ 21 ]. Similar lung deposition data were reported by Nord et al in a scintigraphy study conducted with healthy piglets (1.2–2.2 kg) treated with the same drug/device combination [ 18 ]. In this study, mean lung deposition rates after nebulization during either nCPAP or nasal intermittent positive pressure ventilation (nIPPV) were 15.9% and 21.6%, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The authors reported that this intrapulmonary surfactant deposition sufficed to revert the respiratory distress in surfactant-depleted adult rabbits [ 21 ]. Similar lung deposition data were reported by Nord et al in a scintigraphy study conducted with healthy piglets (1.2–2.2 kg) treated with the same drug/device combination [ 18 ]. In this study, mean lung deposition rates after nebulization during either nCPAP or nasal intermittent positive pressure ventilation (nIPPV) were 15.9% and 21.6%, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…To circumvent this limitation, the most common approach for evaluating the delivery of aerosolized drugs relies on the estimation of the lung deposition from in vitro tests [ 11 , 12 , 13 , 14 ], in vivo preclinical studies [ 15 , 16 , 17 , 18 ], or mathematical modeling [ 19 ]. Most of these studies evaluated the overall drug deposition by quantifying the overall amount of aerosol that impacts against the walls of the different extra pulmonary components of the system (i.e., connecting tubes, patient interface, nebulizer chamber, and patients upper airways), the particles exhaled into the expiratory limb of the ventilation circuit, and the particles delivered into the lung [ 12 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anyhow, irrespective of the CPAP interface used, if the nebulizer was placed between the Y-piece and the CPAP interface, delivering a nominal surfactant dose of 200 mg/kg surfactant, yielded a LD of approximately 28 mg/kg. According to our previous experience with the customized eFlow Neos nebulizer, a nominal dose of 200 mg/kg of surfactant achieved a lung deposition ranging between 8% and 27% in healthy piglets managed with non-invasive ventilation, as estimated from gamma scintigraphy images [27]. The same nominal dose reverted the respiratory distress induced by repeated broncho-alveolar lavages in a rabbit model of acute respiratory distress syndrome [17].…”
Section: Discussionmentioning
confidence: 95%
“…Gregory et al found a surfactant lung deposition of 11.4% in non-human primates (4.8-6.8 kg), managed with a CPAP of 5 cmH 2 O after delivering radiolabeled Lucinactant aerosols generated with a capillary aerosol generator through nasal prongs [31]. Linner et al reported lung depositions of 15.9% of technetium-labeled surfactant (nominal dose 200 mg/kg) in healthy neonatal piglets (1.2-2.2 kg) managed with nasal CPAP (3 cmH 2 O) delivered with customized nasal prongs [32]. Interestingly, the Linner study was conducted with the eFlow Neos nebulizer, the same nebulizer device used in the present study.…”
Section: Discussionmentioning
confidence: 99%